TECHNOLOGY AND CULTURE AND THE PROBLEM OF THE HOMELESS. - Lovekin, David (Philosophical Forum)
The article offers the author's insights concerning the concepts of technology, culture, and the problems of homeless individuals. The author considers technology as a milieu and a system by which one may live. He argues that culture serves as a place for individuals with common world formed by their symbolic embrace of otherness. Moreover, he relates homelessness on the views by historian Christopher Lasch concerning narcissism.